Penentuan Peluang Usaha Pertanian Holtikultura Menggunakan Simple Additive Weighting dan Promethee - Yogi Hermawan; Dedih .; Yessy Yanitasari (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
One of the agriculture sectors that can be used as business opportunities is the vegetable commodity horticultural agriculture sector. There are 5 criteria that can be used, namely the analysis of initial capital, operational costs, harvest time, selling price and profits. While there are 12 kinds of plants namely shallots, green cayenne peppers, green mustard greens, round green eggplants, squash / cucumber, cucumber, long beans, spinach, kale, tomatoes, cauliflower and bitter melon / bitter melon. The implementation of Decision Support System (SPK) to determine horticultural farming business opportunities can be done using the Simple Additive Weighting (SAW) and Promethee methods. The SAW method calculates the value of each criterion, the weight of the criteria and the type of criteria that can be determined by the user himself and the method of method used to determine the order of priority. The SAW method calculates the value of each criterion, the weight of the criteria and the type of criteria that can be determined by the user himself and the promethee methods used to determine the order of priority. The results of this study are getting the highest priority value is spinach plants by 78.1% based on data processed in June 2019 in Karawang district with business analysis in an area of 23 x 2 meters.